(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the Age of Enlightenment, various definitions of enlightenment, the distinctive characteristics of the enlightenment period, and the socio-political ideas of the enlighteners. Additionally, it examines the issues of knowledge as discussed in the ’Avesta,’ which represents the initial stage of the formation of the Age of Knowledge in Eastern philosophy.